Natural forests exhibit higher carbon sequestration and lower water consumption than planted forests in China. (6th November 2018) - Yu, Zhen; Liu, Shirong; Wang, Jingxin; Wei, Xiaohua; Schuler, Jamie; Sun, Pengsen; Harper, Richard; Zegre, Nicolas
Abstract: Large‐scale planted forests (PF) have been given a higher priority in China for improving the environment and mitigating climate change relative to natural forests (NF). However, the ecological consequences of these PF on water resource security have been less considered in the national scale. Moreover, a critically needed comparison on key ecological effects between PF and NF under climate change has rarely been conducted. Here, we compare carbon sequestration and water consumption in PF and NF across China using combination of remote sensing and field inventory. We found that, on average, NF consumed 6.8% (37.5 mm per growing season) less water but sequestered 1.1% (12.5 g C m −2  growing season −1 ) more carbon than PF in the period of 2000–2012. While there was no significant difference in water consumption ( p =  0.6) between PF and NF in energy‐limited areas (dryness index [DI] < 1), water consumption was significantly ( p <  0.001) higher in PF than that in NF in water‐limited regions (DI > 1). Moreover, a distinct and larger shift of water yield was identified in PF than in NF from the 1980s to the 2000s, indicating that PF were more sensitive to climate change, leading to a higher water consumption when compared with NF. Our results suggest NF should be properly valued in terms of maximizing the benefits of carbon sequestration and water yield. Future forest plantation projects should be planned with caution, particularly in water‐limited regions where they might have less positive effect on carbon sequestration but lead to significant water yield reduction. Abstract : While there was no significant difference in water consumption between PF and NF in energy‐limited areas (dryness index < 1), water consumption was significantly higher in PF than that in NF in water‐limited regions (dryness index > 1). NF should be properly valued in terms of maximizing the benefits of carbon sequestration and water yield. Future forest plantation projects should be planned with caution, particularly in water‐limited regions where they might have less positive effect on carbon sequestration but lead to significant water yield reduction.